How i survive Vizmom: a guide for everyday living - Bhatnagar, Vidhu (Chennai Notion press, 2018)
This book handles the complex subject of a working mother's various resources and techniques of handling her stress of working as a busy doctor, along with the responsibility of giving good upbringing to her children.
Keywords: Story